Factors associated with delayed onset of active labor following vaginal misoprostol administration among women at Mbarara Regional Referral Hospital, Uganda - Kajabwangu, Rogers; Bajunirwe, Francis; Lukabwe, Henry; Atukunda, Esther Cathyln; Mugisha, Dale; Lugobe, Henry Mark; Nakalinzi, Joanita; Mugyenyi, Godfrey Rwambuka (My University, 2020)
Methods: We conducted a prospective cohort study over 6 months at a tertiary hospital in Uganda. We enrolled mothers with gestational age ≥28 weeks, who were undergoing labor induction with 50 micrograms of vaginal misoprostol, administered every 6 hours with a maximum of 4 doses and followed them up until onset of active labor. Labor onset was considered delayed if it occurred later than 12 hours after the first dose. Bivariate and multivariate analysis was done to determine factors associated with delayed onset of active labor. Results: Of the 88 mothers enrolled, 22.7% (n=20) had delayed onset of active labor. Nulliparity (aRR: 2.34, 95% CI:1.17-4.68) and gestational less than 37 weeks (aRR: 3.79,95% CI:1.40-10.23) were associated with delayed onset of active labor following vaginal misoprostol administration while higher BMI (aRR: 0.38, 95% CI:0.18- 0.79) decreased the risk. Conclusion: Delayed onset of active labor following labor induction remains an important obstetric care challenge. Mothers undergoing labor induction should have their BMI documented while nulliparous and mothers at gestational age <37 weeks should have labor monitored for a longer duration following labor induction.
Delayed onset of active labor following vaginal misoprostol administration among women
Keywords: Labor; Misoprostol; Onset; Vaginal